Severe Plasmodium falciparum malaria in some Nigerian children - Nmorsi, Onyebiguwa P.G.; Ukwandu, Nnamdi C.D.; Oladokun, Ismaila A.A.; Elozino, Solomon. E. (Journal of Pediatric Infectious Diseases, 2007)
Severe malaria has varying patterns and the relative contributions to individual symptoms to mortality differ with endemicity, geographic locations, access to health services, age but the clinical spectrum has not been described in our study area. Between January 2005 and February 2006, symptoms and signs of severe malaria and the fatality rate among 124 febrile children less than 5 years in Agbor, Delta State, Nigeria were investigated using World Health Organization (WHO) criteria for severe malaria, microscopic parasitemia and standard hematological methods. Fever (100%) was the most frequent symptom encountered among the children diagnosed as severe malaria, while muscle and joint pains (16.1%) were the least common symptoms. The most common sign was severe anemia (100%), while abnormal posture (10.5%) was the least frequent sign in these children. They also had malnutrition (96.8%) associated with severe malaria. Using the WHO criteria for definition of severe malaria, eight clinical features namely severe anemia (100%), malnutrition (96.8%), prostration (87.1%), respiratory distress (55.6%), splenomegaly (38.7%), multiple seizures (44.4%), jaundice (27.1%), and impaired consciousness (20.2%) were reported among the children. Patients were hypoglycemic as reflected in the mean blood glucose of 61.7 ± 0.2 mg/dL. The fatality rate among the children was 6.5% comprising 2/60, (3.3%) children below 12 months and 6/64, (9.4%) children above 12 months. The multivariate analysis showed that children below 12 months old had increased risk of hepatomegaly [Odds ration (OR) = 2.1, 95% confidence interval (CI) 2.0–3.5], splenomegaly (OR = 0.43, 95% CI 0.0–0.71), impaired consciousness (OR = 0.37, 95% CI 0.0–0.88), while children above 12 months of age had increased risk in respiratory distress (OR = 0.19, 95% CI 0.0–0.71) and multiple seizures (OR = 0.27, 95% CI 0.0–0.89). Hypoglycemia malnutrition, prostration, multiple seizures, respiratory distress, leukopenia and severe anemia with poor prognostic values are predictors of fatal outcome of severe malaria in our locality study.
Keywords: Severe malaria; Plasmodium falciparum; child; hematological parameter; Nigeria